2012
DOI: 10.1007/s00520-011-1374-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of end-of-life care for patients with metastatic non-small-cell lung cancer in general wards and palliative care units in Japan

Abstract: Patients with metastatic NSCLC in general wards receive inappropriate care near the end of life. Further studies are needed to develop interventions for making decisions regarding end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Cancer patients are more likely to sign a DNR order than noncancer patients. [17] Previous studies in Taiwan reported that the percentage of critically ill patients signing DNR orders in the intensive care unit was 65.8% to 77.0% in total and 99.8% in cancer patients, respectively. [18,19] Although hospice and palliative medicine was primarily developed to support incurable cancer patients, the need for hospice and palliative care in noncancer patients increases rapidly and becomes a very important issue in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients are more likely to sign a DNR order than noncancer patients. [17] Previous studies in Taiwan reported that the percentage of critically ill patients signing DNR orders in the intensive care unit was 65.8% to 77.0% in total and 99.8% in cancer patients, respectively. [18,19] Although hospice and palliative medicine was primarily developed to support incurable cancer patients, the need for hospice and palliative care in noncancer patients increases rapidly and becomes a very important issue in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that early intervention with palliative treatment improves the quality of life, including quality of terminal care, in patients with non-small cell lung cancer (20,25). According to the abovementioned studies, there were no differences in the number of regimens of chemotherapy administered, between those who were provided early intervention with palliative treatment and those without early intervention with palliative treatment.…”
Section: Discussionmentioning
confidence: 91%
“…However, patients who discontinued treatment early exhibited a longer survival time. Nakano et al (25) reported that the rate of cancer progression and adverse events of chemotherapy are the major causes of differences in the period from discontinuation of chemotherapy to death; they also reported that it is possible to predict the disease progression to some extent during chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to an increased interest with regards to the earlier integration as well as official endorsement by clinical guidelines [43]. Yet, many patients with advanced (lung) cancer either receive such care at a late stage and the quality of such care may not be optimal [44,45]. Although the use of a short screening tool cannot substitute careful clinical assessment and management, routine use of the DT may aid clinicians in identifying those patients at risk for poor outcomes and provide a vantage point from which to earlier engage patients and caregivers in patient-centered conversations about advance care planning and palliative care options.…”
Section: Discussionmentioning
confidence: 99%